PENGARUH MEDIA TUMBUH DAN CUKA ORGANIK PADA PERTUMBUHAN SEMAI PULAI (Alstonia scholaris) - Eva, Yoseva; Ekamawanti, Hanna Artuti; Ekyastuti, Wiwik (JURNAL HUTAN LESTARI, 2019)
Pulai (Alstonia scholaris) is a local species and fast-growing plant that can be used in plantation development activities. The aim of this study was to obtain information on the growth and quality response of seedlings on growing media (a mixture of ultisol, cocopeat, chicken manure and husk charcoal) and organic vinegar (wood vinegar, peat vinegar and fern root vinegar). The research was carried out at the Kasa Rumah Pamer Room and Orchid Market Institute for Research and Service to the Tanjungpura University Community and at the Silviculture Laboratory of the Faculty of Forestry. This study uses an experimental method with split plot design with a completely randomized design (CRD) archetype. The treatment consisted of two factors, namely growth media (ultisol + cocopeat + chicken manure and ultisol + cocopeat + chicken manure + husk charcoal) as the main factor and organic vinegar (chemical fertilizer, peat vinegar, wood vinegar and fern root vinegar) as plot factor. The results showed that the mixed media of ultisol + cocopeat + chicken manure significantly affected the height of pulai seedlings by 55.4 cm (1.28 fold), 6.7 mm diameter (3.35 times) and number of seedling leaves 62 , 25 (1.34 times) of planting media with rice husk charcoal. Organic vinegar has no significant effect on the growth and value of the quality of pulai seed quality index.Keywords: growing media, organic vinegar, pulai seedlings